Dampak model problem based learning pada kemampuan pemecahan masalah matematis - Farwati, Serlin; Sariningsih, Ratna; Hendriana, Heris (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2024)
The motivation behind this investigation was the weak performance of children in math problems. The purpose of this study is to determine the impact of problem-based learning model on improving students' ability to solve mathematical problems. This study utilized a quasi-experiment method with a Nonequivalent Control Group design. The subjects in this study were class VII B as the experimental group and class VII C as the control group. Each of the two classes had thirty-five students.  The purpose of using a control group as a comparison is to observe what symptoms appear in the group of participants who receive treatment. The conclusion shows that the Problem Based Learning model has a significant impact on the average N-Gain score based on the variation between the pretest score and the final score, namely the posttest score, where the average N-Gain score of the experimental and control classes is significantly different.